The pharmaceutical suitcase trade and the need for multisectoral regulation-unproven COVID-19 (Ivermectin and HCQ remedies unmask an insidious health danger in a Caribbean Island) - Maharaj, Sandeep Bhupendra; Dookeeram, Darren; Hosein, Roger; Ramkissoon, Kelvin; Ramdass, Amrica; Franco, Darleen Y.; Pooransingh, Shalini (Frontiers in Public Health, 2024)
This article seeks to highlight an aspect of the illegal pharmaceutical trade in the Caribbean. With the advent of COVID-19 there has been a shortage of a number of drugs in the formal sector. This is largely due to restrictions on foreign exchange, importation delays and sensationalized reporting of unrecommended drugs having a curative effect on COVID-19 patients. This article examines the issue of “the informal suitcase trading” of these drugs. It posits a need for a collaborative and multi-sectoral approach to mitigate the negative effects of the practice on health, trade and national security.